Industrial Training Online Survey System (ITOS) / Nur Yushini Afina Mohd Zuki - Mohd Zuki, Nur Yushini Afina (2017)
Industrial Training is refers to a program which aims to provide supervised practical training within a specified timeframe. So, every each of the student in UiTM especially student from CS230 and CS244 will do internship at the organization choose by them at the end of the semester. When they done the internship, they will be evaluate by their supervisor. Currently, the process of evaluation is done manually which is the process is not too convenient. After done the evaluation, the evaluation form will be submit to the coordinator for coordinator record. The other problem exist is supervisor delaying submitted of the evaluation form and also the time consuming to key-in the data received by the coordinator. Therefore, in order to solve the problem exist ITOS was proposed to help the flow of process evaluation become smooth and more convenient. The target user of ITOS is student, coordinator and the supervisor at the organization. However, methodology plays an important role to develop the high-quality system. The methodology used is Rapid Application Development. The phases of methodology such as requirement planning, user design, construction and cutover are carefully followed to ensure the system flows going well. Furthermore, the result from user evaluation of six construct shows that the highest mean with the same value is ease of learning which 3.80 (SD=0.41). While, the lowest mean is user satisfaction which 3.00(SD=0.00). The future enhancement is providing the statistical graphical data in the system.